Mozambioside Degrades during Coffee Roasting into Newly Identified Pyrolysis Compounds with Lower Activation Thresholds for Bitter Receptors - Coline Bichlmaier; Antonella Di Pizio; Maik Behrens; Roman Lang (Proceedings)
As a global commodity with profound economic and social impact, coffee’s uniqueness is rooted in its distinctive flavor profile, characterized by roasty odors and a bitter taste. Mozambioside, a diterpene glucoside predominantly found in Arabica coffee, has emerged as a potent activator of human bitter receptors TAS2R43 and TAS2R46, exhibiting a bitterness threshold ten times lower than caffeine. The roasting process degrades mozambioside into new compounds. The roasting products were purified from model pyrolysis using liquid chromatographic techniques and their structures were elucidated and characterized by time-of-flight mass spectrometry (MS) and nuclear magnetic resonance spectroscopy. Mozambioside and its roasting products were quantified by targeted UHPLC-MS/MS in coffee powders and brews. Bitter receptor activation was investigated in HEK 293T-Gα16gust44 cells in terms of activation threshold and dose-response. Receptor activation thresholds of the major roasting products 11-O-β-D-glucosyl-(S)-16-desoxy-17-oxocafestol-2-on, 11-O-β-D-glucosyl-15,16-dehydrocafestol-2-on, 11-O-β-D-glucosyl-(R)-16-desoxy-17-oxocafestol-2-on, and bengalensol were lower than those of mozambioside. Molecular Modelling clarified the protein–molecule interaction. The compounds were formed during coffee roasting, reaching their maximum concentration in the final roasting grade. Quantitative analyses revealed that the degradation products were quantitatively extracted from the powder into the brew. During roasting, mozambioside undergoes degradation, giving rise to new compounds with a lower activation threshold for bitter receptors, putatively contributing to the bitterness of Arabica coffee brews. Advanced analytical techniques provide insights into the intricate chemistry underlying coffee’s unique flavor profile.